Scheduling in supply chains using mixed integer programming - Sawik, Tadeusz (Hoboken, N.J. : Wiley, 2011)
A unified, systematic approach to applying mixed integer programming solutions to integrated scheduling in customer-driven supply chains Supply chain management is a rapidly developing field, and the recent improvements in modeling, preprocessing, solution algorithms, and mixed integer programming (MIP) software have made it possible to solve large-scale MIP models of scheduling problems, especially integrated scheduling in supply chains. Featuring a unified and systematic presentation, Scheduling in Supply Chains Using Mixed Integer Programming provides state-of-the-art MIP mo.
Frontmatter -- Short-Term Scheduling in Supply Chains. Scheduling of Flexible Flow Shops -- Scheduling of Surface Mount Technology Lines -- Balancing and Scheduling of Flexible Assembly Lines -- Loading and Scheduling of Flexible Assembly Systems -- Medium-Term Scheduling in Supply Chains. Customer Order Acceptance and Due Date Setting in Make-to-Order Manufacturing -- Aggregate Production Scheduling in Make-to-Order Manufacturing -- Reactive Aggregate Production Scheduling in Make-to-Order Manufacturing -- Scheduling of Material Supplies in Make-to-Order Manufacturing -- Selection of Static Supply Portfolio in Supply Chains with Risks -- Selection of a Dynamic Supply Portfolio in Supply Chains with Risks -- Coordinated Scheduling in Supply Chains. Hierarchical Integration of Medium- and Short-Term Scheduling -- Coordinated Scheduling in Supply Chains with a Single Supplier -- Coordinated Scheduling in Supply Chains with Assignment of Orders to Suppliers -- Coordinated Scheduling in Supply Chains without Assignment of Orders to Suppliers -- References -- Index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Assembly-line methods -- Data processing; Business logistics -- Data processing; Production scheduling -- Data processing; Integer programming; x; Logistique (Organisation) -- Informatique; Ordonnancement (Gestion) -- Informatique; Programmation en nombres entiers; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Assembly-line methods -- Data processing; Business logistics -- Data processing; Integer programming; Production scheduling -- Data processing; Wachtrijtheorie; Ketenbeheer (logistiek); dissertations; Academic theses; Academic theses; 2